Pro iPhone Development with Swift 4 Design and Manage Top Quality Apps - Maskrey, Molly (Apress, 2018)
Acquire and master the information required to take you to the next level beyond basic iPhone development using Swift. In this follow up work to the best selling Beginning iPhone Development with Swift, you'll learn how to improve your apps by managing the performance of your programs using parallelization, getting data in and out of the cloud, using gestures, the camera, 3D touch, sensors as well as newer features having debuted this year. In its fourth edition, Pro iPhone Development with Swift 4 covers the additional information you want to know to extend your apps into the next level.